A cement adhesive and its preparation method and application

By using aluminate cement, artificial porcelain sand, silicon micro powder, silicon carbide and epoxy resin in cement adhesives, the compressive strength and flexural strength are coordinated to improve the compressive strength and flexural strength, the problem of insufficient performance of existing cement adhesives is solved and significant strength improvement is achieved.

CN119059784BActive Publication Date: 2025-03-07NEI MENG GU CHAO GAO YA GONG DIAN JU
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411569975.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-07
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

In the manufacturing and application of existing cement adhesives, the compressive strength and flexural strength of porcelain insulators are poor, making it difficult to meet the high performance needs.

Method used

Components such as aluminate cement, artificial porcelain sand, silicon micro powder, silicon carbide and epoxy resin are used to improve the compressive strength and flexural strength of the cement adhesive through synergistic action.

Benefits of technology

The compressive strength and flexural strength of cement adhesive were significantly improved, and the compressive strength and flexural strength in 28 days were increased by 14% and 30% respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119059784B_ABST
    Figure CN119059784B_ABST
Patent Text Reader

Abstract

The present invention provides a cement adhesive and a preparation method and application thereof, belonging to the technical field of cement adhesives. The cement adhesive provided by the present invention comprises the following components: aluminate cement, artificial porcelain sand, silicon micropowder, admixture and water; the admixture comprises silicon carbide and epoxy resin. In the present invention, silicon carbide and epoxy resin can synergistically improve the compressive strength and flexural strength of the cement adhesive, wherein the epoxy resin has excellent bonding properties and strength, can be tightly combined with the cement matrix to form a strong composite, and can fill the pores of the cement matrix during the curing process to reduce the formation of voids and cracks; the addition of silicon carbide further refines the structure, making the pores smaller and evenly distributed, significantly improving the overall hardness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement adhesives, and in particular relates to a cement adhesive and a preparation method and application thereof. Background Art

[0002] In UHV power transmission systems, porcelain insulators play a vital role. Cement adhesives for porcelain insulators play a key role in the manufacturing and application of porcelain insulators, and are a key part in improving the performance of porcelain insulators. Cement adhesives can not only fix the structure of porcelain insulators and improve electrical performance, but also enhance their corrosion resistance, anti-dumping, anti-vibration and other properties, ensuring the safe and reliable operation of porcelain insulators in power systems. Domestic manufacturers generally use river sand and polycarboxylic acid, in which case the compressive strength and flexural strength of porcelain insulators are poor. Therefore, how to improve cement adhesives to improve compressive strength and flexural strength has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0003] The purpose of the present invention is to provide a cement adhesive and a preparation method and application thereof. The cement adhesive provided by the present invention can improve the compressive strength and flexural strength.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0006] The external dopant includes silicon carbide and epoxy resin.

[0007] Preferably, the mass of the aluminate cement is 40-60% of the total mass of the aluminate cement, artificial porcelain sand and silica powder.

[0008] Preferably, the mass of the artificial porcelain sand is 30-50% of the total mass of aluminate cement, artificial porcelain sand and silica powder.

[0009] Preferably, the mass of the silicon carbide is 0.1-0.5% of the total mass of the aluminate cement, artificial porcelain sand and silicon powder.

[0010] Preferably, the diameter of the silicon carbide is 50-100 nm.

[0011] Preferably, the mass of the epoxy resin is 3-5% of the total mass of the aluminate cement, artificial porcelain sand and silica powder.

[0012] Preferably, the admixture further comprises an anti-cracking agent, a water reducing agent, an antifreeze agent and a defoaming agent; and the water reducing agent is an antifreeze type polycarboxylate water reducing agent.

[0013] Preferably, the water-cement ratio of the cement adhesive is 0.20-0.25.

[0014] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:

[0015] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0016] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.

[0017] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, silicon micropowder, an admixture and water; the admixture comprises silicon carbide and epoxy resin. In the present invention, silicon carbide and epoxy resin can synergistically improve the compressive strength and flexural strength of the cement adhesive, wherein the epoxy resin has excellent bonding performance and strength, can be tightly combined with the cement matrix to form a strong composite, and can fill the pores of the cement matrix during the curing process to reduce the formation of voids and cracks; the addition of silicon carbide further refines the structure, making the pores smaller and evenly distributed, and significantly improving the overall hardness and wear resistance. Experimental results show that the shrinkage rate of the cement adhesive provided by the present invention is 0.043% at 3 days, and the elastic modulus is 38.26 GPa; the shrinkage rate at 7 days is 0.067%, and the elastic modulus is 38.55 GPa; the shrinkage rate at 11 days is 0.068%, and the elastic modulus is 38.36 GPa; the shrinkage rate at 28 days is 0.072%, and the elastic modulus is 38.73 GPa; under standard curing, the compressive strength and flexural strength of the cement adhesive at 28 days are increased by 14% and 30% respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Example 1;

[0019] Figure 2 is the flexural strength of the cement adhesive prepared in Example 1 and Comparative Example 1;

[0020] Figure 3 The compressive strength of the cement adhesive prepared in Example 2 and Comparative Examples 2-3;

[0021] Figure 4 The flexural strength of the cement adhesive prepared in Example 2 and Comparative Examples 2-3;

[0022] Figure 5 is the compressive strength of the cement adhesives prepared in Example 3 and Comparative Examples 4 to 6;

[0023] Figure 6 It is the flexural strength of the cement adhesive prepared in Example 3 and Comparative Examples 4-6. DETAILED DESCRIPTION

[0024] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0025] The external dopant includes silicon carbide and epoxy resin.

[0026] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0027] In the present invention, the cement binder comprises aluminate cement; the aluminate cement is preferably aluminate cement having a strength grade not lower than CA50-II in GB / T 201-2015. In the present invention, the aluminate cement is a matrix material.

[0028] In the present invention, the cement binder further comprises artificial porcelain sand; the particle size of the artificial porcelain sand is preferably 0.3-2 mm. In the present invention, the artificial porcelain sand has uniform particle size and shape, a narrow particle size distribution range, and a smooth particle surface. Compared with traditional river sand aggregate, the artificial porcelain sand has better particle distribution and filling performance, can improve the density and strength of cement, reduce pores and defects in cement, and improve the durability and crack resistance of cement.

[0029] In the present invention, the cement binder further comprises silicon micropowder; the particle size of the silicon micropowder is preferably 0.1-0.3 μm. In the present invention, the silicon micropowder in the cement binder can significantly improve the mechanical properties and durability of the cement binder.

[0030] Taking the total mass of aluminate cement, artificial porcelain sand and silica powder as 100%, the mass content of aluminate cement is preferably 40-60%; the mass content of artificial porcelain sand is preferably 30-50%; and the mass of silica powder is preferably the remainder. In the present invention, limiting the content of aluminate cement, artificial porcelain sand and silica powder within the above range can further improve the compressive strength and flexural strength of cement adhesive.

[0031] As an implementation mode, based on the total mass of aluminate cement, artificial porcelain sand and silica powder as 100%, the mass content of the aluminate cement can be 50-55%; the mass content of the artificial porcelain sand can be 40-48%; and the mass content of the silica powder can be 2%.

[0032] In the present invention, the cement adhesive further includes an admixture; the admixture includes silicon carbide and epoxy resin. In the present invention, silicon carbide and epoxy resin can synergistically improve the compressive strength and flexural strength of the cement adhesive, wherein the epoxy resin has excellent bonding properties and strength, can be tightly combined with the cement matrix to form a strong composite, and can fill the pores of the cement matrix during the curing process to reduce the formation of voids and cracks; the addition of silicon carbide further refines the structure, making the pores smaller and evenly distributed, significantly improving the overall hardness and wear resistance.

[0033] In the present invention, the mass of the silicon carbide is preferably 0.1-0.5% of the total mass of aluminate cement, artificial porcelain sand and silicon powder; the diameter of the silicon carbide is preferably 50-100 nm. The present invention limits the mass of silicon carbide to the above range to further improve the compressive strength and flexural strength of the cement adhesive.

[0034] As an implementation mode, the mass of the silicon carbide can be 0.2-0.4% of the total mass of the aluminate cement, artificial porcelain sand and silicon micropowder, and can also be 0.3%.

[0035] In the present invention, the mass of the epoxy resin is preferably 3-5% of the total mass of aluminate cement, artificial porcelain sand and silica powder; the number average molecular weight of the epoxy resin is preferably 600-2000Da. In the present invention, limiting the mass of the epoxy resin within the above range can further improve the compressive strength and flexural strength of the cement adhesive.

[0036] In the present invention, the external admixture preferably further includes an anti-cracking agent, a water reducing agent, an antifreeze agent and a defoaming agent.

[0037] In the present invention, the anti-cracking agent is preferably polypropylene fiber; the length of the polypropylene fiber is preferably 5-7 mm; the aspect ratio of the polypropylene fiber is preferably 5-10; the mass of the anti-cracking agent is preferably 0.1-3% of the total mass of aluminate cement, artificial porcelain sand and silica powder. In the present invention, the anti-cracking agent is polypropylene fiber, which can improve the anti-cracking performance of cement adhesive, adapt to the low temperature in high-cold areas, and also improve the impact resistance and improve the anti-cracking performance of concrete; in addition, it can also form a mesh structure to prevent the generation and expansion of cracks, improve the anti-cracking performance of cement adhesive, and extend the service life of porcelain insulators.

[0038] As an implementation mode, the length of the polypropylene fiber can be 6 mm; the mass of the anti-cracking agent can be 0.5-2% of the total mass of aluminate cement, artificial porcelain sand and silica powder.

[0039] In the present invention, the water reducer is preferably an antifreeze type polycarboxylate water reducer; the mass of the water reducer is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and silica powder. In the present invention, the antifreeze type polycarboxylate water reducer can significantly improve the fluidity of cement, which is beneficial to the uniform distribution and filling of cement.

[0040] In the present invention, the water reducer is preferably a polycarboxylic acid water reducer with acrylic acid / methacrylic acid as the main chain or a polycarboxylic acid water reducer with maleic anhydride as the main chain. The present invention has no particular limitation on the source of the water reducer, and a high-efficiency water reducer well known to those skilled in the art can be used.

[0041] As an implementation mode, the mass of the water reducing agent may be 0.1-0.2% of the total mass of the aluminate cement, artificial porcelain sand and silica powder.

[0042] In the present invention, the antifreeze agent is preferably polyethylene oxide; the number average molecular weight of the polyethylene oxide is preferably 10 5 ~10 6 The mass of the antifreeze agent is preferably 0.1-0.5% of the total mass of aluminate cement, artificial porcelain sand and silica powder. In the present invention, the antifreeze agent can improve the antifreeze effect of cement adhesive.

[0043] As an implementation mode, the mass of the antifreeze agent may be 0.2-0.4% of the total mass of aluminate cement, artificial porcelain sand and silica powder.

[0044] In the present invention, the defoamer is preferably a polyether defoamer; the mass of the defoamer is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and silica powder. In the present invention, the defoamer can improve the surface tension of cement, reduce the surface pores and foam of cement adhesive, and improve the density and quality; at the same time, the defoamer can also improve the fluidity and plasticity of cement and improve the overall uniformity.

[0045] As an implementation mode, the mass of the defoaming agent can be 0.1-0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder.

[0046] In the present invention, the cement binder further comprises water. In the present invention, the water-cement ratio of the cement binder is preferably 0.20 to 0.25. In the present invention, the water is a solvent.

[0047] As an implementation mode, the water-cement ratio may be 0.22-0.24.

[0048] In the present invention, silicon carbide and epoxy resin can synergistically improve the compressive strength and flexural strength of cement adhesive. Among them, epoxy resin has excellent bonding performance and strength, can be tightly combined with cement matrix to form a strong composite, and can fill the pores of cement matrix during the curing process to reduce the formation of voids and cracks; the addition of silicon carbide further refines the structure, making the pores smaller and more evenly distributed, and significantly improving the overall hardness and wear resistance.

[0049] The cement adhesive provided by the present invention is suitable for use in high-altitude cold areas. By introducing a high-efficiency water reducing agent, artificial porcelain sand, an anti-cracking agent and a defoaming agent, its compressive strength and flexural strength can be further improved, the elastic modulus can be improved, and the shrinkage rate of the cement adhesive can be reduced.

[0050] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:

[0051] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0052] The present invention has no special limitation on the mixing operation of the aluminate cement, artificial porcelain sand, silica powder, admixture and water, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0053] The preparation method provided by the invention has simple process and is suitable for industrial production.

[0054] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.

[0055] In the present invention, the cement adhesive is preferably coated with a buffer layer on the surface of the anti-pollution type porcelain insulator in high-cold areas before application; the material of the buffer layer is preferably asphalt. The present invention has no special limitation on the thickness of the buffer layer, and an operation familiar to those skilled in the art is adopted. In the present invention, there is a difference in thermal expansion coefficient between the anti-pollution type porcelain insulator in high-cold areas and the cement adhesive interface, and the use of a buffer layer can mitigate the difference in thermal expansion coefficient.

[0056] The present invention has no special limitation on the operation of applying the cement adhesive to the anti-pollution porcelain insulator in high-cold areas, and the operation well known to those skilled in the art can be adopted.

[0057] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] The components of cement adhesive are: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0060] The external admixtures are silicon carbide, epoxy resin, anti-cracking agent, water reducing agent, antifreeze agent and defoaming agent;

[0061] The mass of the aluminate cement is 50% of the total mass of the aluminate cement, artificial porcelain sand and silica powder, and the model is CA50-Ⅱ aluminate cement;

[0062] The mass of the artificial porcelain sand is 48% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.3-2 mm;

[0063] The mass of the silica powder is 2% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.2 μm;

[0064] The mass of the silicon carbide is 0.4% of the total mass of aluminate cement, artificial porcelain sand and silicon micropowder; the diameter of the silicon carbide is 50-100 nm;

[0065] The mass of the epoxy resin is 4% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the number average molecular weight is 1000Da;

[0066] The anti-cracking agent is polypropylene fiber, with a length of 6 mm, an aspect ratio of 6, and a mass of 0.5% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0067] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0068] The antifreeze agent is polyethylene oxide with a molecular weight of 2×10 5 , the mass is 0.1% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0069] The defoamer is polyether polyol defoamer SGR1810, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0070] The water-cement ratio of the cement binder is 0.24;

[0071] The preparation method of the cement adhesive is:

[0072] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0073] Comparative Example 1

[0074] On the basis of Example 1, the type of water reducer was changed to naphthalene-based water reducer FDN, and other conditions remained unchanged.

[0075] The cement adhesive prepared in Example 1 and Comparative Example 1 was subjected to performance tests, and the flexural strength, compressive strength, shrinkage rate test, etc. were conducted in accordance with JB / T 4307-2004 "Cement adhesive for insulator assembly"; the fluidity of the cement adhesive was tested in accordance with GB / T 2419-2005 "Method for determination of fluidity of cement mortar", and the results are shown in Tables 1-2. Figure 1 and Figure 2 As shown; Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Example 1, Figure 2 The flexural strength of the cement adhesive prepared in Example 1 and Comparative Example 1.

[0076] Table 1 Performance data of cement adhesives prepared in Example 1 and Comparative Example 1

[0077]

[0078] Table 2 Performance data of cement adhesives prepared in Example 1 and Comparative Example 1

[0079]

[0080] From Table 1~2, Figure 1 and Figure 2 It can be seen that under standard curing, the strength of the cement adhesive prepared by the present invention is significantly improved. After modification, the compressive strength and flexural strength at 28 days are increased by 14% and 30% respectively, and the shrinkage rate is also reduced by 39.0%.

[0081] Example 2

[0082] The components of cement adhesive are: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0083] The external admixtures are silicon carbide, epoxy resin, anti-cracking agent, water reducing agent, antifreeze agent and defoaming agent;

[0084] The mass of the aluminate cement is 50% of the total mass of the aluminate cement, artificial porcelain sand and silica powder, and the model is CA50-Ⅱ aluminate cement;

[0085] The mass of the artificial porcelain sand is 48% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.3-2 mm;

[0086] The mass of the silica powder is 2% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.2 μm;

[0087] The mass of the silicon carbide is 0.4% of the total mass of aluminate cement, artificial porcelain sand and silicon micropowder; the diameter of the silicon carbide is 50-100 nm;

[0088] The mass of the epoxy resin is 4% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the number average molecular weight is 1000Da;

[0089] The anti-cracking agent is polypropylene fiber, with a length of 6 mm, an aspect ratio of 6, and a mass of 2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0090] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0091] The antifreeze agent is polyethylene oxide with a molecular weight of 2×10 5 , the mass is 0.1% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0092] The defoamer is polyether polyol defoamer SGR1810, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0093] The water-cement ratio of the cement binder is 0.25;

[0094] The preparation method of the cement adhesive is:

[0095] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0096] Comparative Example 2

[0097] On the basis of Example 2, the artificial porcelain sand is replaced by river sand with a particle size of 0.2 mm, and the anti-cracking agent polypropylene fiber is omitted, while other conditions remain unchanged.

[0098] Comparative Example 3

[0099] On the basis of Example 2, the artificial porcelain sand was replaced with river sand with a particle size of 0.2 mm, and other conditions remained unchanged.

[0100] The performance of the cement adhesive prepared in Example 2 and Comparative Examples 2-3 was tested according to the testing method of Example 1. The results are shown in Tables 3-4. Figure 3 and Figure 4 As shown, Figure 3 is the compressive strength of the cement adhesive prepared in Example 2 and Comparative Examples 2-3, Figure 4 It is the flexural strength of the cement adhesive prepared in Example 2 and Comparative Examples 2-3.

[0101] Table 3 Performance data of cement adhesives prepared in Example 2 and Comparative Examples 2-3

[0102]

[0103] Table 4 Performance data of cement adhesives prepared in Example 2 and Comparative Examples 2-3

[0104]

[0105] From Table 3~4, Figure 3 and Figure 4 It can be seen that artificial porcelain sand improves the compressive strength and flexural strength of cement adhesive, with the maximum increase of 8.0MPa and 2.7MPa respectively.

[0106] Example 3

[0107] On the basis of Example 2, the mass of silicon carbide was modified to 0.5% of the total mass of aluminate cement, artificial porcelain sand and silicon micropowder, and other conditions remained unchanged.

[0108] Comparative Example 4

[0109] Based on Example 3, silicon carbide and epoxy resin are omitted, and other conditions remain unchanged.

[0110] Comparative Example 5

[0111] Based on Example 3, the epoxy resin was omitted, the content of silicon carbide was changed to 4.5%, and other conditions remained unchanged.

[0112] Comparative Example 6

[0113] On the basis of Example 3, silicon carbide was omitted, the content of epoxy resin was changed to 4.5%, and other conditions remained unchanged.

[0114] The cement adhesives prepared in Example 3 and Comparative Examples 4 to 6 were tested for performance according to the testing method of Example 1. The compressive strength of the cement adhesives prepared in Example 3 and Comparative Examples 4 to 6 was as follows: Figure 5 As shown, the flexural strength of the cement adhesives prepared in Example 3 and Comparative Examples 4 to 6 is as follows Figure 6 shown.

[0115] from Figure 5 and 6 It can be seen that silicon carbide and epoxy resin can synergistically improve the compressive strength and flexural strength of cement adhesive.

[0116] Example 4

[0117] The components of cement adhesive are: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0118] The external admixtures are silicon carbide, epoxy resin, anti-cracking agent, water reducing agent, antifreeze agent and defoaming agent;

[0119] The mass of the aluminate cement is 60% of the total mass of the aluminate cement, artificial porcelain sand and silica powder, and the model is CA50-Ⅱ type aluminate cement;

[0120] The mass of the artificial porcelain sand is 30% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.3-2 mm;

[0121] The mass of the silica powder is 10% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.2 μm;

[0122] The mass of the silicon carbide is 0.1% of the total mass of aluminate cement, artificial porcelain sand and silicon micropowder; the diameter of the silicon carbide is 50-100 nm;

[0123] The mass of the epoxy resin is 5% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the number average molecular weight is 1000Da;

[0124] The anti-cracking agent is polypropylene fiber, with a length of 6 mm, an aspect ratio of 6, and a mass of 3% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0125] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.1% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0126] The antifreeze agent is polyethylene oxide with a molecular weight of 2×10 5 , the mass is 0.5% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0127] The defoamer is polyether polyol defoamer SGR1810, and its mass is 0.1% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0128] The water-cement ratio of the cement adhesive is 0.20;

[0129] The preparation method of the cement adhesive is:

[0130] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0131] Example 5

[0132] The components of cement adhesive are: aluminate cement, artificial porcelain sand, silica powder, admixture and water;

[0133] The external admixtures are silicon carbide, epoxy resin, anti-cracking agent, water reducing agent, antifreeze agent and defoaming agent;

[0134] The mass of the aluminate cement is 40% of the total mass of the aluminate cement, artificial porcelain sand and silica powder, and the model is CA50-Ⅱ type aluminate cement;

[0135] The mass of the artificial porcelain sand is 50% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.3-2 mm;

[0136] The mass of the silica powder is 10% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the particle size is 0.2 μm;

[0137] The mass of the silicon carbide is 0.3% of the total mass of aluminate cement, artificial porcelain sand and silicon micropowder; the diameter of the silicon carbide is 50-100 nm;

[0138] The mass of the epoxy resin is 3% of the total mass of aluminate cement, artificial porcelain sand and silica powder, and the number average molecular weight is 1000Da;

[0139] The anti-cracking agent is polypropylene fiber, with a length of 6 mm, an aspect ratio of 6, and a mass of 1% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0140] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.3% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0141] The antifreeze agent is polyethylene oxide with a molecular weight of 2×10 5 , the mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0142] The defoamer is polyether polyol defoamer SGR1810, and its mass is 0.3% of the total mass of aluminate cement, artificial porcelain sand and silica powder;

[0143] The water-cement ratio of the cement binder is 0.22;

[0144] The preparation method of the cement adhesive is:

[0145] Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

[0146] The performance of the cement adhesives prepared in Examples 4-5 was tested according to the testing method of Example 1. The results are shown in Tables 5-6.

[0147] Table 5 Performance data of cement adhesives prepared in Examples 4 to 5

[0148]

[0149] Table 6 Performance data of cement adhesives prepared in Examples 4-5

[0150]

[0151] It can be seen from Tables 5 and 6 that under standard curing, the cement adhesive prepared by the present invention has excellent mechanical properties.

[0152] It can be seen from the above embodiments and comparative examples that the cement adhesive provided by the present invention can improve the compressive strength and flexural strength.

[0153] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cement adhesive, characterized in that: It is composed of the following components: aluminate cement, artificial porcelain sand, silica powder, admixture and water; The external doping agent includes silicon carbide and epoxy resin; The mass of the silicon carbide is 0.1-0.5% of the total mass of aluminate cement, artificial porcelain sand and silicon powder; The mass of the epoxy resin is 3-5% of the total mass of aluminate cement, artificial porcelain sand and silica powder; The preparation method of the cement adhesive comprises: Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

2. The cement adhesive according to claim 1, characterized in that: The mass of the aluminate cement is 40-60% of the total mass of the aluminate cement, artificial porcelain sand and silica powder.

3. The cement adhesive according to claim 1, characterized in that: The mass of the artificial porcelain sand is 30-50% of the total mass of aluminate cement, artificial porcelain sand and silica powder.

4. The cement adhesive according to claim 1, characterized in that: The diameter of the silicon carbide is 50-100 nm.

5. The cement adhesive according to claim 1, characterized in that: The external admixture also includes an anti-cracking agent, a water reducing agent, an antifreeze agent and a defoaming agent; the water reducing agent is an antifreeze type polycarboxylate water reducing agent.

6. The cement adhesive according to claim 1, characterized in that: The water-cement ratio of the cement adhesive is 0.20-0.

25.

7. The method for preparing the cement adhesive according to any one of claims 1 to 6, characterized in that: include: Aluminate cement, artificial porcelain sand, silica powder, admixture and water are mixed to obtain cement adhesive.

8. Use of the cement adhesive according to any one of claims 1 to 6 or the cement adhesive prepared by the preparation method according to claim 7 in anti-pollution porcelain insulators in high-cold areas.

Citation Information

Patent Citations

  • Epoxy resin modified cement-based adhesive and preparation method thereof

    CN108409233A

  • Application of silicon carbide whisker in preparation of wear-resistant toughened anti-crack cement-based material

    CN112456906A

  • Cement adhesive as well as preparation method and application thereof

    CN116425479A

  • Extra-high voltage cylindrical head suspension porcelain insulator high-alumina cement adhesive and preparation method thereof

    CN117843327A